Factors Associated With Physician Recommendation of Home Blood Pressure Monitoring and Blood Pressure in the US Population. (15th June 2020) - Tang, Olive; Foti, Kathryn; Miller, Edgar R; Appel, Lawrence J; Juraschek, Stephen P
Abstract: BACKGROUND: Hypertension guidelines recommend home blood pressure monitoring (HBPM) to help achieve blood pressure (BP) control. We hypothesized that HBPM use with a physician recommendation would be associated with lower BP and greater medication adherence. METHODS: We used data from 6, 320 adults with hypertension in the National Health and Nutrition Examination Survey 2009–2014 to characterize the association of (i) provider recommendation for HBPM and (ii) HBPM use on 2 outcomes: measured BP (linear regression) and medication adherence (logistic regression). Provider recommendation, HBPM use, and medication use were self-reported. RESULTS: Among adults with hypertension, 30.1% reported a physician recommendation for HBPM, among whom 82.0% reported using HBPM. Among those who did not report a physician recommendation for HBPM, 28.3% used HBPM. Factors associated with a physician recommendation were having health insurance, higher education attainment, hypertension awareness, and having a prescription for antihypertensive medication. Among those who reported receiving a physician recommendation, those who used HBPM had a mean BP that was 3.1/4.5 mm Hg lower than those who did not. Those who reported having a physician recommendation and using HBPM were more likely to report hypertension medication adherence (odds ratio 2.9; 95% confidence interval: 2.0, 4.4). CONCLUSIONS: HBPM use was associated with lower BP and higher medication adherence. Use of HBPM was higher among those with a physician recommendation. These results support a role for physicians in counseling and partnering with patients on HBPM use for BP management.